On the Existence and Stability of Periodic Solutions for a Nonlinear Neutral Functional Differential Equation. (31st March 2013) - Yuan, Yueding; Guo, Zhiming
Abstract : This paper deals with the existence and stability of periodic solutions for the following nonlinear neutral functional differential equation (d / d t) D u t = p ( t ) - a u ( t ) - a q u ( t - r ) - h ( u ( t ), u ( t - r ) ) . By using Schauder-fixed-point theorem and Krasnoselskii-fixed-point theorem, some sufficient conditions are obtained for the existence of asymptotic periodic solutions. Main results in this paper extend the related results due to Ding (2010) and Lopes (1976).